Excretion and Residual Concentration Correlations of Salbutamol Between Edible Tissues and Living Samples in Pigs and Goats - Sun, Lei; Zhu, Minjuan; Shi, Jingfei; Mi, Kun; Ma, Wenjing; Xu, Xiangyue; Wang, Hanyu; Pan, Yuanhu; Tao, Yanfei; Liu, Zhenli; Huang, Lingli (Frontiers in Pharmacology, 2021)
Illegal use of salbutamol (SAL), a β-adrenergic leanness-enhancing agent, has posed potential threat to human health in China. The excretion and depletion of SAL in pigs and goats were investigated, and the concentration correlations between edible tissues and living samples were analyzed to find out a suitable living sample for pre-slaughter monitoring of SAL in pigs and goats. After a single oral dosage of 1.2 mg/kg SAL, approximately 70% of the dose was excreted by pigs and goats from their excreta. When pigs and goats were supplied feed containing SAL (20 mg/kg) for 14 consecutive days, high concentrations of SAL were observed in the liver and kidneys, and the longest persistence was observed in hair. Unlike pigs, SAL was presented primarily as conjugated SAL in goats. Excellent concentration correlations of SAL were observed between urine and edible tissues both in pigs and goats, and in addition, good correlations also were found between hair and edible tissues in pigs and between feces and edible tissues in goats. Hence, urine and hair could accurately predict SAL concentrations in edible tissues of pigs, whereas feces and urine were satisfactory for predicting SAL concentrations in edible tissues of goats. These data make it possible for pre-slaughter monitoring of SAL residues in the edible tissues of pigs and goats.